GAMBARAN SPIRITUALITY AT WORK PADA DOSEN DI JAKARTA - Andi Januar; Maria Dwi Yanika Hesti Nugraha (Psibernetika, 2014)
College as an educational institution has an important role in education. Aside from being a bridge for the transformation of knowledge, the college is also in charge of creating human beings are skilled and reliable in the face of the real working world. In order to achieve these objectives, the role of the lecturer as an educator at the college is very important.In this case spirituality at work is needed to improve the quality of the lecture. Spirituality at work is one of the psychological climate in which people who work have an internal life that nourishes and nurtured by meaningful work, and feeling connected with others and with the community in workplace. Purpose of this study is to describe spirituality at work on lectures in Jakarta. The method used is descriptive method, a method in researching the status of a group of people, an object, condition, thought, or an event in the present, the goal is to create a description, picture, or painting in a systematic, factual and accurate information on the facts-facts, properties and relationships between the phenomena investigated. The results obtained in this study is spirituality at work on lectures in Jakarta who are in the high category with the percentage is 28.83%, with the validity of .30 and reliability of .940. Keywords: Spirituality, Sprituality at work, lecturers